2012
DOI: 10.3109/00016489.2012.743031
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and mortality trends of head and neck cancer in Croatia in the period 1988–2008

Abstract: HNC incidence and mortality in men declined steadily during the study period (estimated annual percent change (EAPC) of -1.5% and -1.8%, respectively). The most prominent decreases of -5.7% annually for incidence and -9.3% for mortality were observed in the youngest age group, 30-39 years. A non-significant increase in incidence (EAPC 0.9%) and decrease in mortality (EAPC -1.3%) were observed in women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 11 publications
1
6
0
1
Order By: Relevance
“…The importance of tobacco and alcohol on laryngeal cancer mortality is also reflected by the similarity of trends to those for lung cancer and other tobacco‐and alcohol‐related neoplasms . Moreover, as reported in a few other studies, over the last few decades declines were also observed in laryngeal cancer incidence, influenced by changes in risk factors exposures only, in the absence of populations programs of screening for the disease. Thus, the steady decrease and the changes in tobacco use in subsequent generations of European men largely explains the fall in male laryngeal cancer mortality in several countries, particularly in middle‐age .…”
Section: Discussionsupporting
confidence: 57%
“…The importance of tobacco and alcohol on laryngeal cancer mortality is also reflected by the similarity of trends to those for lung cancer and other tobacco‐and alcohol‐related neoplasms . Moreover, as reported in a few other studies, over the last few decades declines were also observed in laryngeal cancer incidence, influenced by changes in risk factors exposures only, in the absence of populations programs of screening for the disease. Thus, the steady decrease and the changes in tobacco use in subsequent generations of European men largely explains the fall in male laryngeal cancer mortality in several countries, particularly in middle‐age .…”
Section: Discussionsupporting
confidence: 57%
“…Kopf-Hals-Tumoren "wahrscheinlich HPV-assoziierter" Lokalisationen zeigten einen jährlichen Anstieg der Inzidenzraten sowohl bei Männern (JPV: + 3,3 %; KI[0,2; 6,6]) als auch bei Frauen 2006 2007 2008 2009 2000 2001 2002 2003 2004 2005 2006 2007 2008 2009 2 000 2001 2002 2003 2004 2005 2006 2007 2008 2009 2000 2001 2002 2003 2004 2005 2006 2007 2008 2009 Abb. [21], Dänemark [22], Großbritannien [23], Kroatien [24], Schweden [25] und den Niederlanden [26]. Der Rückgang der Inzidenz von Larynx-und Hypopharynxkarzinomen in westlichen Ländern wird mit dem sinkenden Tabakkonsum in Verbindung gebracht, die Zunahme der Inzidenz von Oropharynxtumoren hingegen mit HPV-Infektionen [27].…”
Section: Plattenepithelkarzinome Und Hpv-assoziationunclassified
“…Over the past few decades, however, there has been a rise in HPV+ OPSCC [5,1214]. In Croatia the trend between 1988 and 2008 was showing decreasing overall incidence of HNSCC [15], with more recent data corroborating the trend [4]. The proportion of HPV associated OPSCC is now approximately 70% in the developing countries, which is a substantial increase from previous rates [5,16].…”
Section: Introductionmentioning
confidence: 99%
“…In Croatia, only clinical guidelines for the treatment of laryngeal cancer currently exist, which is only a subset of HNSCC, accounting for ~33% of HNSCC cases in the country, while there are no guidelines for the treatment of cancers arising at other head-and-neck sites [15]. As HPV involvement seems to drive the increase of OPSCC incidence in developed countries, establishing guidelines for this cancer type could be of a future benefit to patients, but the baseline data for such guidelines are scarce.…”
Section: Introductionmentioning
confidence: 99%